Development of a forensically important fly, Megaselia scalaris (Loew) (Diptera: Phoridae) on cow’s Liver and various agar-based diets - Raja Muhammad Zuha,; Supriyani Mustamin,; Balkhis Bashuri,; Nazni Wasi Ahmad,; Baharudin Omar, (penerbit ukm, 2012)
In forensic entomology practice, it is more common to use raw animal tissue to breed dipteran larvae and it often brings unpleasant odour in the laboratory. Few studies suggested the use of synthetic diets, mainly agar-based media, as alternatives to animal tissue but it is rarely being practiced in forensic entomology laboratory. The present study observed the growth of a forensically important fly, Megaselia scalaris (Loew) on raw cow’s liver, nutrient agar, casein agar and cow’s liver agar. A total of 100 M. scalaris eggs were transferred each into the different media and placed in an incubator at 30°C in a continuous dark condition. Data on length and developmental period were collected by randomly sampling three of the largest larvae from each rearing media, twice a day at 0900 and 1500 hours until pupariation. M. scalaris larvae reared on raw cow’s liver recorded the highest mean length (4.23 ± 1.96 mm) followed by cow’s liver agar (3.79 ± 1.62 mm), casein agar (3.14 ± 1.16 mm) and nutrient agar (3.09 ± 1.11 mm). Larval length in raw liver and liver agar were significantly different from those in nutrient and casein agar (p < 0.05). Larvae bred in liver agar and raw liver recorded the shortest larval duration before entering the post-feeding stage (89 hours), followed by nutrient agar (119 hours) and casein agar (184 hours). Total developmental time from oviposition until adult emergence for M. scalaris in liver agar and raw liver was approximately 163 hours. All puparia in nutrient agar and casein agar failed to hatch. This research highlighted the potential use of cow’s liver agar as an alternative diet of raw liver to culture M. scalaris in laboratory